Application of Guided Inquiry Learning Model to Improve Junior High School Students' Science Process Skills - Choirunnisa', Marsyanda Alfina; Rosdiana, Laily (Science Education and Application Journal, 2023)
The purpose of this study was to describe the improvement of students' science process skills towards the guided inquiry learning model of class VIII at SMPN 2 Semen. The method used in this research is descriptive quantitative with the type of research used quasi experiment using one treatment class, namely class VIII-E totaling 35 students. The research design used one group pretest posttest design. The data collection technique in this study used the test method. Science process skills after applying the guided inquiry learning model on the vibration and mechanical wave sub-material have increased. The percentage of completeness for post-test scores was 80%. Class VIII-E obtained an N-Gain score of 0.6 in the medium category. Thus it can be concluded that the guided inquiry learning model can improve students' science process skills.